Enriching students’ language skills for grade 8 - Cerna, Glory Mei Sabandal (Electronic Journal of Education, Social Economics and Technology, 2023)
This study assessed the five language skills such as listening, speaking, reading, writing, and viewing and tested their significant relationship with the Grade 8 students’ Average English Grades at Guihulngan National High School-Poblacion, Negros Oriental, school year 2018-2019. Based on the findings, enrichment activities were proposed. The descriptive method was utilized in interpreting the data gathered from the rating sheets showing the students’ English grades, and the adapted questionnaire, testing the skills. Simple Percentage, Weighted Mean, MPS, and T-test were used as statistical tools. The Grade 8 students were Fairly Satisfactory in listening, speaking, and viewing, while they Did Not Meet Expectations in reading and writing. Overall, their performance level was Fairly Satisfactory. Additionally, it was disclosed that the majority or 48 percent of the respondents obtained the general average of Fairly Satisfactory. Moreover, the test of significance revealed that listening, speaking, viewing, and writing have a positive significant relationship with the students’ English grades. However, reading skill was found to have no significant relationship with the students’ grades though both variables possess a positive low correlation. Based on the findings, it can be said that the English Performance level of the Grade 8 students was far below the standard set by the Department of Education which an is Outstanding level, and that Grade in English was a determinant of the Performance level of the respondents. Thus, it is highly recommended that the output of this study be implemented.